Princípios constitucionais da seguridade social - Pereira Filho, Luiz Clemente (2006)
The present work aims at promoting a review of the foundation principles and rules of the social security in the Republican Letter of 1988, with the objective to establish an interpretation that allows maximum effectiveness on its application, by means of the disruption of the national doctrine s traditional trend to attribute greater importance and normative effectiveness to the principles, relegating the rules to a secondary role. We begin the work with the historical analysis of the social security, as well as with the analysis of the delineation that the Constitution gives to this social politics, this essential public service. Following, the premise that the social security constitutes a true social basic right is fixed. From the inevitable consequences of the interpretation of this premise, as the subjective and objective effectiveness of the basic rights, and from a differentiation between the kinds of norms based on the Theory of the Principles of Humberto Ávila that rejects its hierarchical organization and is established in its own different way of application we point which constitutional devices regarding social security present characteristics of rules or principles. From this point, we go along the analysis of these norms, beginning from those that relate to the expenditure, that is, from the principles of the financial and actuarial balance , of the fairness on the participation of the expenditure , of the diversity of the financing base . Following, the norms relative to the benefits are approached: the principles of the universality of the covering and the attendance , of the uniformity and equivalence of the benefits and services to the urban and rural populations , of the selectivity and distributiveness in the rendering of benefits and services and of the irreducibility rule of the value of the benefits , finishing at approaching the norms relative to the organization of the system, more specifically the principles of the unicity and of the democratic and decentralized management of the system , trying to disclose its main possibilities of interpretation, also by means of the analysis of the rules and related principles. In this task, examples of the national legislative and jurisprudential production are presented on respecting or not its orders. Especially the legislative and jurisprudential production is evaluated as regards to what Humberto Ávila considers a third normative species, the postulates norms that structuralize the relation between norms , in special the postulate of the proportionality, instrument of verification of the validity of a relation between means and end, that reveals a special suitability for control of adequacy of the norms relative to the social security, either regarding the expenditure financing/protection , or the benefits rendering/repairing